Due process of law beyond the state : requirements of administrative procedure - Della Cananea, Giacinto (Oxford : Oxford University Press, 2016)
Analysing both national and transnational processes, this volume offers an integrated viewpoint of the principles governing the procedural due process requirements of regional and global regulatory regimes.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on October 28, 2016).
Keywords: Administrative procedure; Law; Laws of specific jurisdictions & specific areas of law